2009
DOI: 10.1158/1078-0432.ccr-09-0728
|View full text |Cite
|
Sign up to set email alerts
|

Low p27 Expression Predicts Early Relapse and Death in Postmenopausal Hormone Receptor–Positive Breast Cancer Patients Receiving Adjuvant Tamoxifen Therapy

Abstract: Purpose: Previously, we have shown that p27 may be a potential predictive biomarker for the selection of premenopausal women with early-stage hormone-responsive breast cancer for adjuvant endocrine therapy. The purpose of the present study was to assess the clinical relevance of p27 expression in postmenopausal hormone receptor-positive breast cancer patients who were treated with adjuvant tamoxifen therapy. Experimental Design: We determined the expression of p27 by immunohistochemistry in the surgical specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Based on the mechanism of PPM1H, this trend is consistent with many studies in the literature that have established low p27 expression and high SKP2 expression as poor prognostic indicators in breast cancer (26,(37)(38)(39)(40)(41)(42)(43)(44). Furthermore, the cell-cycle inhibitory activity of p27 on cyclin E/CDK2 complexes can be abrogated by cyclin D/CDK4, which binds p27 and titrates it away from cyclin E/CDK2.…”
Section: Preparation Of Recombinant Ppm1hsupporting
confidence: 87%
“…Based on the mechanism of PPM1H, this trend is consistent with many studies in the literature that have established low p27 expression and high SKP2 expression as poor prognostic indicators in breast cancer (26,(37)(38)(39)(40)(41)(42)(43)(44). Furthermore, the cell-cycle inhibitory activity of p27 on cyclin E/CDK2 complexes can be abrogated by cyclin D/CDK4, which binds p27 and titrates it away from cyclin E/CDK2.…”
Section: Preparation Of Recombinant Ppm1hsupporting
confidence: 87%
“…27,28 Recent studies have demonstrated that p27(Kip1) is a predictive factor for Tam treatment response in premenopausal and postmenopausal women with breast cancer. 29,30 In contrast to other tumor suppressor proteins, p27 expression levels in tumor cells are frequently regulated by ubiquitin-dependent proteolysis, which is controlled by the phosphorylation of p27 at a conserved threonine (T187) and facilitates polyubiquitylation of p27; this prevents binding to its critical cellular targets such as the cyclin E/Cdk2 and A/Cdk2 complexes. In addition, the phosphorylation of p27 by AKT and SRC kinases at either T157 (AKT) or tyrosine 74/88 (SRC) induces cellular mislocalization or functional inactivation, which disables p27 as a tumor suppressor protein.…”
Section: Discussionmentioning
confidence: 99%
“…P27kip1 is a well-known tumor suppressor gene, its expression levels have both prognostic and therapeutic implications [13][14][15][16][17][18]. In this study, we intend to validate p27KIP1 expression levels as a predictive marker for the response of rapalogs based on primary breast cancer cells and patientderived breast tumor xenograft models.…”
Section: Discussionmentioning
confidence: 99%